Deregulated origin licensing leads to chromosomal breaks by rereplication of a gapped DNA template - Neelsen, Kai J; Zanini, Isabella M Y; Mijic, Sofija; Herrador, Raquel; Zellweger, Ralph; Ray Chaudhuri, Arnab; Creavin, Kevin D; Blow, J Julian; Lopes, Massimo (Genes & development, 2013)
Deregulated origin licensing and rereplication promote genome instability and tumorigenesis by largely elusive mechanisms. Investigating the consequences of Early mitotic inhibitor 1 (Emi1) depletion in human cells, previously associated with rereplication, we show by DNA fiber labeling that origin reactivation occurs rapidly, well before accumulation of cells with >4N DNA, and is associated with checkpoint-blind ssDNA gaps and replication fork reversal. Massive RPA chromatin loading, formation of small chromosomal fragments, and checkpoint activation occur only later, once cells complete bulk DNA replication. We propose that deregulated origin firing leads to undetected discontinuities on newly replicated DNA, which ultimately cause breakage of rereplicating forks.